2008
DOI: 10.1016/j.mce.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-independent prostate cancer cells acquire the complete steroidogenic potential of synthesizing testosterone from cholesterol

Abstract: The proliferation and differentiation of normal prostate epithelial cells depends upon the action of androgens produced by the testis. Prostate cancers retain the ability to respond to androgens in the initial stages of cancer development, but progressively become independent of exogenous androgens in advanced stages of the disease while maintaining the expression of functional androgen receptor (AR). In the present study, we have determined the potential of prostate cancer cells to synthesize androgens from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 26 publications
10
175
1
3
Order By: Relevance
“…39 It has recently been shown that prostate cancer cells in advanced stages can synthesize androgens directly from cholesterol. 40 These findings might explain the suggested association between serum cholesterol levels and risk of aggressive forms of prostate cancer. Future studies are needed to confirm the exact role of cholesterol and other blood lipids in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 92%
“…39 It has recently been shown that prostate cancer cells in advanced stages can synthesize androgens directly from cholesterol. 40 These findings might explain the suggested association between serum cholesterol levels and risk of aggressive forms of prostate cancer. Future studies are needed to confirm the exact role of cholesterol and other blood lipids in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 92%
“…Eggs are an important source of cholesterol and choline, both of which are highly concentrated in prostate cancer cells. Cholesterol homeostasis is disrupted in malignant cells, leading to accumulation of cholesterol, which is a precursor of androgen and may alter signaling pathways to promote cancer progression (Freeman et al, 2004;Dillard et al, 2008). Choline is essential for a variety of cell functions involved in cancer growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…[66] Androgen-independent prostate cancer cell lines synthesize testosterone from radio-labeled cholesterol in vitro, and human prostate cancer xenografts are capable of synthesizing DHT from acetate and cholesterol, confirming that tumoral androgen synthesis is possible. [67] Thus, experimental and clinical evidence suggests that the enzymes of steroid metabolism are activated in the prostate cancer with CRPC state, and might provide multiple new targets for therapeutic intervention. Moreover, substantial evidences suggest that CRPC may not, in fact, be androgen independent, but occurs in a setting of continued ARmediated signaling that is driven by the presence of residual tissue androgens.…”
Section: Androgen Milieu In the Castration-resistant Prostate Cancermentioning
confidence: 99%